Blockchain, Cryptocurrency, and Real Estate: The Current Situation and Prospects for the Next 5 Years. Issue 1 (31st December 2022) - Simons, Robert A.; Simons, Samuel T.
Abstract: Blockchain technology is a platform for transactions and investment. It includes Cryptocurrencies, of which there are dozens of investment vehicles. Bitcoin and Ethereum are the best known. Crypto is an emerging asset class and offers some portfolio diversification benefits and attractive return rates. Some crypto investments are stablecoins and are tethered to underlying currencies like the US dollar. Blockchain allows ease of access and transparency and provides a cloak of pseudonymity, which may be incompatible with owning real estate, which generally has ownership and transactions as public records. This article provides a brief primer on the intersection of blockchain, cryptocurrencies, and real property. It reviews the various ways that these emerging technologies and instruments are used in real estate investment today. We investigate a blockchain-oriented investment platform, RealT, and report on their business model and customer-servicing interface. Their model offers tokenized real estate to a wide range of qualified investors, and many of the occupied houses feature secure cash flows in the form of Section 8 tenants. If properly developed, the model appears sustainable and can rejuvenate inner-city residential property markets and open the door for a greater ROE for not-for-profit groups.